A hydrogen pump: Transfer of four hydrogens from a cyclohexane ring to a triple bond during a menthofuran/bromoacetylene adduct rearrangement. Issue 28 (11th July 2019) - Tomilin, Denis N.; Gotsko, Maxim D.; Sobenina, Lyubov N.; Ushakov, Igor A.; Trofimov, Boris A.
Graphical abstract: Highlights: Rearrangement of menthofuran/bromoacetylene [4+2] cycloadducts to benzofuranylpropanones. Facile non-catalytic four-hydrogen transfer from cyclohexane fragment to the triple bond. Acetylenic furan is an intermediate of intramolecular aromatization/saturation process. Abstract: The cycloadducts of menthofuran with acylbromoacetylenes, (3-bromo-1, 6-dimethyl-5, 6, 7, 8-tetrahydro-2 H -2, 4a-epoxynaphthalen-4-yl)(aryl)methanones, rearrange (CHCl3, reflux, 1 h) to 2-(2-acylethyl)benzofurans (along with the expected 2-bromo-3-hydroxy-4, 7-dimethyl-5, 6, 7, 8-tetrahydronaphthalene-1-yl)(aryl)methanones) via 2-acylethynylmenthofurans, thus indicating the exceptionally mild and rapid transfer of four hydrogens from a cyclohexane ring to a triple bond through the furan moiety in the key intermediate 2-acylethynylmenthofuran.